THE EFFECT OF PROVIDING TYPES OF FERTILIZERS THAT DIFFERENT TO THE GROWTH AND SUSTAINABILITY OF THE SEA LIVES OF A NETWORK CULTURE (Eucheuma cottoni) - Jaelani, Muhamad Mahsun; Marzuki, Muhammad; Azhar, Fariq (Jurnal Perikanan Unram, 2021)
Seaweed is one of the potential fishery commodities to be cultivated. One of the seaweed that has a high economic value is Eucheuma cottonii which is a result of tissue culture of carrageenan-producing red algae species and has many important roles for humans. seaweed Eucheuma cottonii. This research was conducted in March-April 2019 in the sea of ??Lombok Sekotong, West Lombok Regency. The method used was RAL (Completely Randomized Design) with 4 treatments and 3 replications. Maintenance media uses sea water added with a dose of 100 grams, namely: P1 (Liquid Fertilizer), P2 (NPK Fertilizer), P3 (Urea Fertilizer) P4 (TSP Fertilizer). The observed data are absolute weight, absolute length, daily growth, relative weight, relative length and water quality used as maintenance media. Data analysis using ANOVA. The results showed that the addition of Liquid Fertilizer, NPK, Urea and TSP with 100 grams dosage had a very significant effect on the growth and survival of Eucheuma cottonii seaweed. The highest growth rate is in Urea fertilizer while the lowest growth is in TSP fertilizer.